Artificial Intelligence and Public Health Systemt - Maher, Nevenka (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The paper shows how artifical intelligence (AI) became a system transformation driver of public health system in European Union in the financial perspective 2021-2027. As AI drives research, development and innovation. European Commission (EC) has in time prepared proper regultation and instruments. However, AI activites delay in some countries (not only in the context of digital transformation, but in the framework of multiple dimensions), what deminishes the contry competitiveness. Following the sustainable development concept, the health of a citizen has a special notion: it is a value and a productivity driver. Only healthy people are productive and perform added value. Added value is a leading driver of growth also in the EC Draghi Report; based on this report, the corections of 2021-2027 strategy is performing and strategy and measures for next financial perspective 2028-2034 will be prepared. That is why this paper is exposing the meaning and AI dimensions of digitisation and AI in the public care system. In this context, activities in Slovenia are described following three startegic questions, as: Are critical challenges of health system in Slovenia identified and capacities for them develped? Does politics put health in the centre of action and its governance? Does the development of AI impact institutional capacities?